Focal Malonate Injection Into the Internal Capsule of Rats as a Model of Lacunar Stroke - Cirillo, Carla; Le Friec, Alice; Frisach, Isabelle; Darmana, Robert; Robert, Lorenne; Desmoulin, Franck; Loubinoux, Isabelle (Frontiers in Neurology, 2018)
Background: Stroke is the first cause of disability in adults in western countries. Infarct of the internal capsule (IC) may be related to motor impairment and poor prognosis in stroke patients. Functional deficits due to medium-sized infarcts are difficult to predict, except if the specific site of the lesion is taken into account. None of the few pre-clinical models recapitulating this type of stroke has shown clear, reproducible and long-lasting sensorimotor deficits. Here, we developed a rat model of lacunar infarction within the IC, key structure of the sensorimotor pathways, by precise injection of malonate. Methods: The mitochondrial toxin malonate was injected during stereotactic surgery into the IC of rat brain. Rats were divided in three groups: two groups received malonate solution at 1.5M, (n=12) or at 3M (n=10) and a sham group (n=3) received PBS. Three key motor functions - usually evaluated following cerebral lesion in the clinic - strength, target reaching, and fine dexterity were assessed in rats by a forelimb grip strength test, a skilled reaching task (staircase) for reaching and dexterity, and single pellet retrieval task. Sensorimotor functions were evaluated by a neurological scale. Live brain imaging, using magnetic resonance (MRI), and post-mortem immunohistochemistry in brain slices were performed to characterize the lesion site after malonate injection. Results: Intracerebral injection of malonate produced a 100% success rate in inducing the lesion in the IC. All rats receiving the toxin, regardless the dose injected, had similar deficits in strength and dexterity of the contralateral forepaw, and showed significant neurological impairment. Additionally, only partial recovery was observed with respect to strength, while no recovery was observed for dexterity and neurological deficit. MRI and immunostaining showed the volume size of the lesion and the precise location in the IC, the destruction of axonal structures and the Wallerian degeneration of fibers in the area above the injection site. Conclusions: This pre-clinical model of lacunar stroke induces a lesion in the IC with measurable and reproducible sensorimotor deficits, and limited recovery with stabilization of performance two weeks post-injury. Future therapies in stroke may be successfully tested with this model.